People Skills in the 21st Century: A Perspective on the Smart City in an Emerging Economy - Tanatorn Tanantong; Papon Moolngearn; Tanpat Kraiwanit; Pongsakorn Limna; Aishath Rafiyya (Human Behavior and Emerging Technologies)
Smart cities are hubs of innovation and rapid development, where technology plays a significant role in shaping the urban environment. In such settings, the ability to adapt and think flexibly is crucial for individuals to thrive. The study’s goal is to understand which factors influence how well individuals are equipped with 21st-century skills and how they apply them in the dynamic context of modern urban living. Employing a quantitative research approach, data were initially collected from 600 Thai respondents through convenience sampling. A subsequent data-cleansing process refined the focus to 568 respondents, selected based on their high-score attainment. The study utilized percentages, means, and binary logistic regression in a comprehensive data analysis. Its key findings illuminate the influence of various factors, including score, age, career trajectory, and engagement with social media platforms like Instagram, LINE, and X, on skill development within the smart city context. This research offers a nuanced perspective on the myriad elements that foster individual and collective success in technologically advanced urban environments. It moves beyond mere acknowledgment of innate abilities or age-related wisdom, highlighting the critical roles of career advancement and digital engagement in skill enhancement. The implications of these findings are far reaching, especially for policymakers, educators, and industry leaders. They underscore the need for a comprehensive approach to shaping the future of urban living and working spaces, ensuring that individuals are not just equipped with the necessary skills but are also adept at applying them effectively in the smart cities of tomorrow. This study serves as a guide for these stakeholders, emphasizing the importance of fostering environments that support continuous learning, innovation, and adaptability in the face of technological advancements.